Bovine papillomavirus type 1 E2 transcriptional regulators directly bind two cellular transcription factors, TFIID and TFIIB. - Rank, N M (1995)
The bovine papillomavirus type 1 (BPV-1) E2 translational open reading frame encodes three proteins that regulate viral transcription and DNA replication: the E2 transcriptional activator (E2TA), the E2 transcriptional repressor (E2TR) and the E8/E2 transcriptional repressor (E8/E2TR). E2TA is a strong activator of papillomaviral promoters and is required for viral DNA replication. E2TR and E8/E2TR inhibit the activities of E2TA but also possess weak transactivational properties of their own. Two components of the cellular transcription apparatus, TFIID and TFIIB, have previously been shown to associate with other viral and cellular transcriptional activators. We present evidence here that E2TA, the full-length E2 open reading frame gene product, directly binds both of these transcription factors in vitro. Glutathione S-transferase E2TA (GST-E2TA) fusion protein bound in vitro-synthesized TATA-box-binding protein (TBP), a component of TFIID, and in vitro-synthesized TFIIB. Likewise, GST-E2TA bound TFIID and TFIIB present in a nuclear extract from the human cervical cancer-derived cell line, HeLa. The binding of GST-E2TA to TBP and TFIIB required no additional mammalian factors, as shown by direct binding of GST-E2TA to bacterially synthesized recombinant TBP and recombinant TFIIB. The domain of E2TA required for its interaction with both TBP and TFIIB was localized to the C terminus of E2TA, a region also present in E2TR and E8/E2TR. This domain lies within the region of E2TA previously shown to confer cooperative DNA binding by E2TA and TBP and overlaps with the region of E2TA required for DNA binding and dimerization. Our findings, taken in context with previous studies, lead us to conclude that (i) cooperative DNA binding by E2 proteins and TBP is likely mediated by the direct binding of E2 proteins to TBP, (ii) the weak transcriptional transactivation by E2TR and E8/E2TR may result as a consequence of direct TBP and TFIIB binding by these proteins, and (iii) TBP and/or TFIIB binding may be required but is not sufficient for E2TA's strong transactivational activity.